Allelopathy of a native shrub can help control invasive grasses at sites under ecological restoration in a Neotropical savanna. (4th July 2018) - Lopes, Polliana G.; Oliveira, Sarah C. Caldas; Salles, Karina A.; Sampaio, Alexandre B.; Schmidt, Isabel B.
ABSTRACT: Background : African C4 grasses threatens newly restored areas in Neotropical savannas. Allelopathy exhibited by some native species may contribute to ecological restoration. Aims : To establish the potential use of Lepidaploa aurea (Asteraceae) in ecological restoration of invaded savannas, we evaluated its allelopathic effects on two invasive grasses, a native grass, and two native trees (one savanna and one riparian forest species). Methods : We tested the allelopathic effects of the leaves and roots of L. aurea in a growth chamber, a greenhouse, and in field experiments. Results : Leaf extracts reduced the growth of all other species in the growth chamber experiment. Root extracts reduced growth in one invasive grass and promoted root growth in the savanna tree. The invasive grass and riparian forest tree were negatively affected when planted in soil where L. aurea had grown, whereas the savanna tree showed increased growth. Lepidaploa aurea litter reduced growth in one invasive grass species and increased root biomass accumulation in the native grass species. Conclusions : Lepidaploa aurea negatively affected the growth of invasive grasses, through plant extracts, litter and through soil. These patterns could explain its ability to colonise abandoned pasturelands and its high success of establishing in restoration areas.